A worldwide survey of MATESOL programs in 2014: Patterns and perspectives. (January 2018) - Stapleton, Paul; Shao, Qing
This article reports on a survey of 241 Master of Arts programs in TESOL (MATESOL) in 16 countries serving as a snapshot of second language teacher education in 2014. After an initial screening by a set of criteria, these programs were first identified, and their course offerings, among other criteria, such as entrance and capstone requirements, were categorized. In total, 3, 877 courses across 15 knowledge fields were coded with frequency counts taken. Our analysis revealed that the most frequently appearing course offerings tended to focus on teaching methods. However, large differences appeared among the programs with regard to the offering of courses in various knowledge fields. Differences also appeared between US and non-US programs, particularly with regard to practicum requirements. Several other patterns and themes emerged from the data including the extensive coverage of social and cultural aspects of language learning in elective courses, and the lack of focus on specific English as a foreign language (EFL) contexts in course offerings, among others.